2019
DOI: 10.1111/apha.13374
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A/C negatively regulated by miR‐124‐3p modulates apoptosis of vascular smooth muscle cells during cyclic stretch application in rats

Abstract: Aim Apoptosis of vascular smooth muscle cells (VSMCs) influenced by abnormal cyclic stretch is crucial for vascular remodelling during hypertension. Lamin A/C, a nuclear envelope protein, is mechano‐responsive, but the role of lamin A/C in VSMC apoptosis is still unclear. Methods FX‐5000T Strain Unit provided cyclic stretch (CS) in vitro. AnnexinV/PI and cleaved Caspase 3 ELISA detected apoptosis. qPCR was used to investigate the expression of miR‐124‐3p and a luciferase reporter assay was used to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…1c). Among these 21 genes, MYC associated factor X [49], Sp1 transcription factor [50], cyclic adenosine monophosphate responsive element binding protein 1 [51], homeobox A4 [52], and estrogen receptor 1 [53] were previously reported to participate in the switch of ASMC phenotype. It was proposed that miR-22-3p might indirectly regulate CHD9 expression via these factors.…”
Section: Discussionmentioning
confidence: 99%
“…1c). Among these 21 genes, MYC associated factor X [49], Sp1 transcription factor [50], cyclic adenosine monophosphate responsive element binding protein 1 [51], homeobox A4 [52], and estrogen receptor 1 [53] were previously reported to participate in the switch of ASMC phenotype. It was proposed that miR-22-3p might indirectly regulate CHD9 expression via these factors.…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 types of cell mechanical stretching methods: sustained [35, 36] and cyclic stretching [44]. We examined the hemodynamic changes of the right common carotid artery proximal to the band in the TAC model and found that the lumen diameter and blood flow were significantly higher than those in the SHAM group in both the diastolic and systolic phases (data not shown), suggesting that the excessive MSS on the vascular adventitia under overload pressure was present in both diastolic and systolic phases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, certain progress has been made in the studies on its effect under circumferential stress. For example, high-cyclic stretch significantly elevated miR-124-3p, downregulating lamin A/C and inducing VSMC apoptosis [28]. Cyclic stretch is an initial factor of vein graft failure; after CABG, the stretch rate of the saphenous vein will be 10-15% due to the pulsating pressure from the aorta [29], which causes over deformation of the endothelium.…”
Section: Discussionmentioning
confidence: 99%